Assessing the Italian benefit corporation disclosure: a content analysis. (13th May 2022) - Palladino, Rosa; Sasso, Pasquale; Profita, Sofia; Carusone, Rosalinda; Fiano, Fabio; Giudice, Manlio Del
Responsible business actions improve corporate performance and contribute to sustainable development practices. These actions must not only be implemented, but also communicated. Therefore, the use of reporting tools based on non-financial data should increase the ability of the company management to implement an integrated strategy. In fact, the legislator has decided to introduce a new corporate formula more oriented towards sustainability: the benefit corporation (CB). This corporate form requires higher standards of accountability to demonstrate their positive impact on society. This document, through a qualitative analysis of some Italian CBs' reports, aims to investigate the effectiveness of the BIA framework to report the 'benefit' objectives. The study shows that the CBs maintain a formal commitment on the disclosure plan and denounces the lack of planning strategies relating to the disclosure provided. This analysis focused on the compatibility of the IIRC framework for integrated reporting to improve the quality of reporting.